Effects of parenting classes and economic strengthening for caregivers on the cognition of HIV-exposed infants: a pragmatic cluster randomised controlled trial in rural Zimbabwe. Issue 5 (11th September 2019) - Mebrahtu, Helen; Simms, Victoria; Mupambireyi, Zivai; Rehman, Andrea M; Chingono, Rudo; Matsikire, Edward; Malaba, Rickie; Weiss, Helen A; Ndlovu, Patience; Cowan, Frances M; Sherr, Lorraine
Abstract : Introduction: HIV-exposed children show signs of developmental delay. We assessed the impact of a pragmatic multicomponent intervention for caregivers of HIV-exposed children aged 0–2 years in Zimbabwe. Methods: We conducted a cluster-randomised trial from 2016 to 2018. Clusters were catchments surrounding clinics, allocated (1:1) to either National HIV guidelines standard of care or standard care plus an 18-session group intervention comprising i) early childhood stimulation (ECS) and parenting training with home visits to reinforce skills and retention in HIV care; ii) economic strengthening. Primary outcomes measured 12 months after baseline (4.5 months postintervention completion) included: i) global child development measured using the Mullen early learning composite score; ii) retention in HIV care. Analysis used mixed effects regression to account for clustering and adjusted minimally for baseline prognostic factors and was by intention to treat. Results: Thirty clusters, 15 in each arm, were randomised. 574 dyads were recruited with 89.5% retained at follow-up. Ninety one of 281 (32.4%) were recorded as having received the complete intervention package, with 161/281 (57.3%) attending ≥14 ECS sessions. There was no evidence of an intervention effect on global child development (intervention mean 88.1 vs standard of care mean 87.6; adjusted mean difference=0.06; 95% CI −2.68 to 2.80; p=0.97) or infant retention in care (proportion of children who had missed their most recent HIV test: intervention 21.8% vs standard of care 16.9%, p=0.18). There was weak evidence that the proportion of caregivers with parental stress was reduced in the intervention arm (adjusted OR (aOR)=0.69; 95% CI 0.45 to 1.05; p=0.08) and stronger evidence that parental distress specifically was reduced (intervention arm 17.4% vs standard of care 29.1% scoring above the cut-off; aOR=0.56; 95% CI 0.35 to 0.89; p=0.01). Conclusion: This multicomponent intervention had no impact on child development outcomes within 4.5 months of completion, but had an impact on parental distress. Maternal mental health remains a high priority. Trial registration number: PACTR201701001387209.